Air conditioner filters become sinks and sources of indoor microplastics fibers. (1st January 2022) - Chen, Yingxin; Li, Xinyu; Zhang, Xiaoting; Zhang, Yalin; Gao, Wei; Wang, Ruibin; He, Defu
Abstract: Indoor airborne microplastics fibers (MPFs) are emerging contaminants of growing concern. Nowadays, air conditioners (ACs) are widely used in indoor environments. However, little is known about their impact on the distribution of indoor MPFs. In this study, we first disclosed the prevalence of MPF contamination in filters for indoor split ACs used in living rooms, dormitories, and offices. The average density of microfibers was 1.47–21.4 × 10 2 items/cm 2, and a total 27.7–35.0% of fibers were MPFs. Of these fibers, the majority were polyester (45.3%), rayon (27.8%), and cellophane (20.1%). We further tracked the long-term accumulation of MPFs on AC filters in three types of rooms, and demonstrated that dormitories showed relatively heavy accumulation especially after running for 35–42 days. Furthermore, we found that simulative AC filters which had been lined with PET MPFs could effectively release those MPFs into indoor air, propelling them away from the ACs at varying distances. Statistical analysis showed that the estimated daily intake of MPFs (5–5000 μm length) from AC filters would increase gradually with their usage, with the intake volume reaching up to 11.2 ± 2.2–44.0 ± 8.9 items/kg-BW/day by the 70th day, although this number varied among people of different ages. Altogether, these findings suggest that AC filters can act as both a sink and a source of microplastics fibers. Therefore, AC filters should be evaluated not only for their substantial impact on the distribution of indoor airborne MPFs, but also for their role in the prevalence of the related health risks. Graphical abstract: Image 1 Highlights: Microplastic fibers (MPFs) were widely detected on AC filters in multiple types of room. MPFs including polyester, rayon and cellophane account for 28–35% fibers on AC filters. MPFs accumulate on AC filters gradually, heavily after usage of 35–42 days. Simulative PET MPFs can effectively release from AC filters, and into indoor air. Estimated daily intake of MPFs increase with AC usage, vary among different age people.